An unusual cause of haematuria - case report - Peixoto, João (2023)
INTRODUCTION: The development of a uretero-arterial fistula (UAF) is a rare and life-threatening condition. Owing to its low prevalence, diagnosis and management remains a challenge for both urologists and vascular surgeons and UAF’s high mortality rates may be at least partially attributed to delayed diagnosis. We present a case of UAF in a patient with previous pelvic surgery and indwelling ureter catheter. CASE REPORT: An 82-year-old male presented to the emergency department with haemodynamic instability and gross haematuria that started one hour prior to admission. The laboratory study performed showed an acute anaemia of 7.5g/dl and a contrast enhanced computed tomography revealed a ureteral fistula betweenthe stented left ureter and the common iliac artery. The patient was taken to the angiography suit and a balloon- expandable stent-graft (GORE® VIABAHN® VBX – 11mm diameter and 59mm in length) was deployed. Following the procedure, the haematuria resolved, and the patient had an uneventful post-operative stay. He was discharged two weeks after admission, following a course of large spectrum antibiotic therapy. The patient remained asymptomatic at 3 month follow up. CONCLUSIONS: Uretero-arterial fistula is an uncommon condition but with an increasing prevalence, at least in part due to improved pelvic cancer treatment.